The Initial Experience of Trans-Rectal Ultrasound and Biopsy in Diagnosis of Carcinoma Prostate In Gezira Hospital For Renal Disease And Surgery (GHRDS) - Walaa Eldin Ibraheem; Sami Mahjoub Taha; Mustafa Omran Mansour; Mohammed El Imam Mohamed Ahmed (Sudan Journal of Medical Sciences)
Background: Prostate cancer prevalent cancer in males above sixty-five worldwide, this lead to the introduction of screening of the PSA and using of the transrectal ultrasound scanning, and sextant biopsy of the prostate.